The Indians of Texas : from prehistoric to modern times - Newcomb, William W. (William Wilmon), 1921-2010 (University of Texas Press, 2007)
Explores the ethnography of the Indian tribes who lived in the region that is now the state of Texas since the beginning of the historic period.